THE IMPACT OF INTEGRATING INFORMATICS AND MATHEMATICS ON STUDENTS’ ALGORITHMIC THINKING - Ergashev Bobur Abdutolibovich (Modern American Journals, 2025)
This article explores the pedagogical impact of integrating informatics and mathematics in secondary and higher education, with a particular focus on enhancing students’ algorithmic thinking. The development of algorithmic thinking is essential for solving complex problems, designing step-by-step solutions, and fostering computational literacy. The integration of informatics and mathematics enables students to understand the logical structure of problems while applying computational tools for resolution. The study presents both theoretical insights and practical approaches for harmonizing these subjects in the curriculum. The research emphasizes the importance of interdisciplinary connections to cultivate deeper reasoning and strengthen problem-solving capacities among learners.
Keywords: Algorithmic thinking, interdisciplinary approach, informatics education, mathematics integration, computational logic, problem-solving skills, digital pedagogy